Marmesin is a novel angiogenesis inhibitor: Regulatory effect and molecular mechanism on endothelial cell fate and angiogenesis. Issue 2 (28th December 2015) - Kim, Jae Hyeon; Kim, Jin-Kyu; Ahn, Eun-Kyung; Ko, Hye-Jin; Cho, Young-Rak; Lee, Choong Hyun; Kim, Yong Kee; Bae, Gyu-Un; Oh, Joa Sub; Seo, Dong-Wan
Abstract: In the present study, we investigated the effects and molecular mechanism of marmesin, a coumarin compound isolated from Broussonetia kazinoki, on vascular endothelial growth factor-A (VEGF-A)-induced endothelial cell responses in vitro and angiogenic sprouting in aortic rings ex vivo . Marmesin treatment inhibited VEGF-A-stimulated endothelial cell proliferation through down-regulation of cell cycle-related proteins including cyclin-dependent kinases and cyclins, leading to pRb hypophosphorylation and G1 phase cell cycle arrest. In addition, marmesin treatment abrogated VEGF-A-induced endothelial cell migration, invasion and capillary-like structure formation in vitro as well as angiogenic sprouting ex vivo . These anti-angiogenic activities of marmesin were mediated through inactivation of VEGF-A-stimulated signaling pathways, and down-regulation of cell surface signaling molecules including VEGF receptor-2, human epidermal growth factor receptor-2, integrin β1 and integrin-liked kinase. Taken together, these findings clearly support the pharmacological roles of marmesin in regulating angiogenesis, and warrant further evaluation and development as a potential therapeutic agent for the treatment and prevention of angiogenesis-related diseases including cancer.